Competitive Advantage Strategy in Facing Challenges and Determinants of Business Continuity (Study on Chockles Beverage Business) - Yusuf Syahiir Habiibii; Susilo Toto Raharjo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The food and beverage business in the city of Semarang every year continues to grow. However, in addition to the growth rate of its business which always grows every year, the number of players (trademarks) also increases both from foreign and local, both franchised and non-franchised which means that the market is narrower because there are more and more new competitors entering, for this reason Chockles must always make breakthroughs in order to develop following a dynamic market so that it is able to continue to compete and remain the choice of the community amid the onslaught of old players and competitors new. The purpose of this study is to increase scientific understanding of how innovations are made and developed in the face of challenges that are being faced as well as those that are coming given uncertain business conditions. This shows that the challenges and determining factors for business continuity are one of the things that influence innovation design in achieving competitive advantage. The number of informants used in this study were owners and employees of Chockles. The method of data collection is by using interview. Data analysis method used is qualitative analysis with interactive model. Based on the research that has been done then it can be obtained the conclusion, for Ferto Group's survival in achieving its goal of becoming a true and trusted distributor company, it is needed a new generation that will be able to lead Ferto Group in the future. Structured and sustainable mentoring will make Ferto Group's company components to have the same consistency and vision of both employees and leaders and in the long run it is expected to change the principal as well. The company's new culture is based on the value of continuous mentoring to instill corporate values to employees.